Post-COVID-19 deep vein thrombosis and its pharmacological management (Research, Society and Development, 2022)
Infection caused by the SARS-CoV-2 coronavirus presents clinical cases that range from asymptomatic to severe. Even in milder cases, sequelae related to a hypercoagulable state associated with COVID-19 can be observed, with an increased prevalence of Venous Thromboembolism (VTE). The occurrence of VTE is higher in patients, mainly patients hospitalized in intensive care units and requires anticoagulation therapy, however, post-COVID thrombogenesis can also occur at a later stage, in the absence of viral load. The prothrombotic mechanisms related to SARS-CoV-2 differ with regard to the use of antiplatelet and anticoagulant drugs in patients with suspected or confirmed COVID-19. The pharmacology and clinical applicability of anticoagulant drugs such as heparins and oral anticoagulants will be described in this study. This study is an exploratory study aiming to address issues related to the treatment hitherto recommended for thrombotic events in patients affected by COVID-19.